Moral Discourse within the Church: An Essential Dimension of Social Communication - Shields, Richard (Communicatio socialis, 2004)
On the background of Catholics facing a crisis in moral leadership in Canada and the United States strengtherred by the revelation of clerical sexual abuse and its cover-up by many bishops, the author points at a discrepancy between the moral teachings of the Church authorities and the indifference of the people. He therefore proposes to examine the question of social communication within the Church for developing an effective moral discourse. Using the insights of social sciences, he shows that sharing moral conscience and knowing socially how to respond to evil and work towards good, is essential to the healty functioning of religion. He suggests to find an effective official structure of moral social communication by fastering "communities of practice", as they are presently known in corporate thinking.